응집·한외여과 공정에서 역세척 조건 결정 및 막오염 특성에 관한 연구 - 문성용; 이상협; 김승현; 이병천; 윤종섭 (한국물환경학회, 2006)
This study is about backwash condition and membrane fouling at continuous coagulation/ultrafiltration process in water treatment. The capacity of pilot plant was 0.06 m3/d. The result of the test, Backwash cycle time and duration time had a significant effect on the efficiency of system and backwash. Backwash duration time was determined to be fixed in 30 seconds for the system with more than 95% recovery rate, It needed 30 minute backwash frequency. During the continuous operation, membrane fouling was analyzed by determining the filtration resistance (Ri) and cake layer resistance (Rc). At the initial stage, filtration resistance highly influenced the fouling behavior. But after 1.5 hours, cake layer resistance became more important than filtration resistant.